2019
DOI: 10.2106/jbjs.oa.19.00027
|View full text |Cite
|
Sign up to set email alerts
|

Total Hip Arthroplasty in a Low-Income Country

Abstract: Background: We describe our 10-year experience performing total hip arthroplasty (THA) in patients enrolled in the National Joint Registry of the Malawi Orthopaedic Association. Methods: Eighty-three THAs were performed in 70 patients (40 male and 30 female) with a mean age of 52 years (range, 18 to 77 years). The cohort included 24 patients (14 male and 10 female; mean age, 52 years [range, 35 to 78 years]) who were human immunodeficiency virus (HIV)-p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
5
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 23 publications
0
5
0
Order By: Relevance
“…Additionally, postoperative outcomes were defined by surgical revision rates and were assessed at 2 years post-THA. This timeframe may not be long enough for statistically significant revision rates to appear in the cohorts, so future studies may consider extending their definition of long-term outcomes to 5 or 10 years as was done in Graham et al 31…”
Section: Discussionmentioning
confidence: 99%
“…Additionally, postoperative outcomes were defined by surgical revision rates and were assessed at 2 years post-THA. This timeframe may not be long enough for statistically significant revision rates to appear in the cohorts, so future studies may consider extending their definition of long-term outcomes to 5 or 10 years as was done in Graham et al 31…”
Section: Discussionmentioning
confidence: 99%
“…Ethical approval has been given to the NARMOA from the Research Ethics Committee of the College of Medicine of the University of Malawi since its inception in 2005. Previous studies by our group using data from the NARMOA of all patients with known HIV status have shown low complication rates and good functional outcomes 9,[25][26][27] .…”
mentioning
confidence: 80%
“…However, these studies have included HIV-positive patients with hemophilia and/or a history of intravenous drug use, which are independent risk factors for joint infection 16,24 . Our previous studies 9,[25][26][27] have demonstrated low complication rates in HIV-positive patients without hemophilia or intravenous drug-use history, and outcomes that are not substantially different than those of HIVnegative patients.…”
mentioning
confidence: 97%
See 1 more Smart Citation
“…4 Various different platforms have been trialed in order to deliver arthoplasty in low-income countries including government sponsored programs, charitable missions with visiting surgeons and development of specialist hospitals either through charitable donations, government funding or a mixture of both. 57 Revision arthroplasty has an increased cost in terms of implants but also increased morbidity to the patients both acutely and in long term functional outcome. In developed healthcare systems the safety and long term outcomes of arthroplasty have been improved through evidence based implant selection, 1,8 stringent infection control measures, advanced recovery protocols and dedicated arthroplasty follow up clinics to identify problems early.…”
Section: Introductionmentioning
confidence: 99%